Electrically and thermally conductive underwater acoustically absorptive graphene/rubber nanocomposites for multifunctional applications. Issue 38 (20th September 2017) - Li, Ying; Xu, Fan; Lin, Zaishan; Sun, Xianxian; Peng, Qingyu; Yuan, Ye; Wang, Shasha; Yang, Zhiyu; He, Xiaodong; Li, Yibin
Abstract : Graphene is ideal filler in nanocomposites due to its unique mechanical, electrical and thermal properties. Abstract : Graphene is ideal filler in nanocomposites due to its unique mechanical, electrical and thermal properties. However, it is challenging to uniformly distribute the large fraction of graphene fillers into a polymer matrix because graphene is not easily functionalized. We report a novel method to introduce a large fraction of graphene into a styrene–butadiene rubber (SBR) matrix. The obtained graphene/rubber nanocomposites were mechanically enhanced, acoustically absorptive under water, and electrically and thermally conductive. The Young's modulus of the nanocomposites was enhanced by over 30 times over that for rubber. The electrical conductivity of nanocomposites was ≤219 S m −1 with 15% volume fraction of graphene content, and exhibited remarkable electromagnetic shielding efficiency of 45 dB at 8–12 GHz. The thermal conductivity of the nanocomposites was ≤2.922 W m −1 k −1, which was superior to the values of thermally conductive silicone rubber thermal interface materials. Moreover, the nanocomposites exhibited excellent underwater sound absorption (average absorption coefficient >0.8 at 6–30 kHz). Notably, the absorption performance of graphene/SBR nanocomposites increased with increasing water pressure. These multifunctional graphene/SBR nanocomposites have promising applications in electronics, thermal management and marine engineering.